Human immunodeficiency virus/Leishmania infantum in the first foci of urban American visceral leishmaniasis: clinical presentation from 1994 to 2010 - Lima,Iúri Paz (2013)
INTRODUCTION:Human immunodeficiency virus (HIV) coinfection with Leishmania infantum or Leishmania donovani, the agents of visceral leishmaniasis (or kala-azar), has become a fatal public health problem in the tropics where kala-azar is endemic.METHODS:The clinical presentation of patients with HIV and L. infantum coinfection is described using two unique databases that together produce the largest case series of patients with kala-azar infected with HIV in South America. First, a retrospective study paired the list of all patients with kala-azar from 1994 to 2004 with another of all patients with HIV/AIDS from the reference hospital for both diseases in the City of Teresina, State of Piauí, Brazil. Beginning in 2005 through to 2010 this information was prospectively collected at the moment of hospitalization.RESULTS:During the study, 256 admissions related to 224 patients with HIV/L. infantum coinfection were registered and most of them were males between 20-40 years of age. Most of the 224 patients were males between 20-40 years of age. HIV contraction was principally sexual. The most common symptoms and signs were pallor, fever, asthenia and hepatosplenomegaly. 16.8% of the cohort died. The primary risk factors associated to death were kidney or respiratory failure, somnolence, hemorrhagic manifestations and a syndrome of systemic inflammation. The diagnosis of HIV and kala-azar was made simultaneously in 124 patients.CONCLUSIONS:The urban association between HIV and kala-azar coinfection in South America is worrisome due to difficulty in establishing the diagnosis and higher mortality among the coinfected then those with either disease independently. HIV/L. infantum coinfection exhibits some singular characteristics and due to its higher mortality it requires immediate assistance to patients and greater research on appropriate combination therapy.